Impact of endodontic case difficulty on operating time of single visit nonsurgical endodontic treatment under general anesthesia - Shin Hye Chung; Juhea Chang (BMC, 2021)
Abstract Background A Case Difficulty Assessment Form was designed for use in endodontic curricula, and to assist practitioners with treatment planning, referral and recording. The aim of this study was to determine how endodontic case difficulty factors influence the operating time of single-visit nonsurgical endodontic treatments under general anesthesia. Methods Data on 198 single-visit endodontic treatments (80 anterior teeth, 43 premolars, and 75 molars) performed under general anesthesia by a specialized practitioner were obtained from 119 special needs patients (mean [SD] age = 30.7 [14.7] years). Total duration of operation was analyzed with relation to demographic and dental factors and American Association of Endodontists (AAE) Case Difficulty Assessment factors. Mann-Whitney U test, t-test, and Kruskal-Wallis test were used to assess relationships between operating time and confounding factors (p < 0.05). Results High difficulty cases required significantly longer time to complete operations than treatments of minimal-to-moderate difficulty regardless of tooth type (p < 0.05). Demographic factors of the patients rarely influenced operating time length. Among variables included in the AAE Case Difficulty Assessment Form, tooth position, crown morphology, root morphology, canal appearance, and periodontal condition were significantly associated with increased operating time (p < 0.05). Conclusions A higher level of case difficulty contributed to increased duration of endodontic treatment under general anesthesia indicating that Endodontic Case Difficulty Assessment Form is useful for predicting the duration of nonsurgical endodontic treatment. Among many factors, complicated anatomic features of the treated teeth increased case complexity and extended operating time.